List cultures : knowledge and poetics from Mesopotamia to BuzzFeed - Young, Liam Cole (Recursions: theories of media, materiality, and cultural techniques., 2017)
We live in an age of lists, from magazine features to online clickbait. This book situates the list in a long tradition, asking key questions about the list as a cultural and communicative form. What, Liam Cole Young asks, can this seemingly innocuous form tell us about historical and contemporary media environments and logistical networks? Connecting German theories of cultural techniques to Anglo-American approaches that address similar issues, 'List Cultures' makes a major contribution to debates about New Materialism and the post-human turn.